Absolute measurements of chlorine Cl+ cation single photoionization cross section. (January 2015) - Hernández, E.M.; Juárez, A.M.; Kilcoyne, A.L.D.; Aguilar, A.; Hernández, L.; Antillón, A.; Macaluso, D.; Morales-Mori, A.; González-Magaña, O.; Hanstorp, D.; Covington, A.M.; Davis, V.; et al.
Abstract: The photoionization of Cl + leading to Cl 2+ was measured in the photon energy range of 19.5–28.0 eV. A spectrum with a photon energy resolution of 15 meV normalized to absolute cross-section measurements is presented. The measurements were carried out by merging a Cl + ion beam with a photon beam of highly monochromatic synchrotron radiation at the Advanced Light Source at Lawrence Berkeley National Laboratory. The measured photoionization of Cl + consists of several autoionization resonances surperimposed on the direct photoionization signal. Most of the prominent resonances are assigned to members of Rydberg series originating from the singlet ground state and from metastable triplet levels within the ground-state configuration of Cl + . The direct ionization cross section is no larger than 12 Mb. Abstract : Highlights: The single photoionization absolute cross section of Cl + ion was measured. Numerous resonances were identified as belonging to Rydberg series. A large population of the metastable Cl + ( 1 D2 ) was identified. Identified resulting Cl 2+ state terms correspond to 2 D5/2 and 2 D3/2 .